Indonesia's Maritime Diplomacy under Joko Widodo Administration: Advancing the Global Maritime Fulcrum Vision - Setiawan, Asep (Jurnal Indonesia Sosial Sains, 2024)
This research examines Indonesia's maritime diplomacy during the administration of President Joko Widodo (2014–2024) within the framework of the Global Maritime Fulcrum (GMF) vision. The research aims to analyze how Indonesia leveraged its maritime diplomacy to project its strategic identity and address challenges such as illegal fishing, maritime boundary disputes, and regional cooperation. Using qualitative analysis of policy documents, official speeches, and multilateral engagements, the study identifies Indonesia's adoption of cooperative, persuasive, and coercive approaches to maritime diplomacy. Results reveal significant progress in fostering regional maritime cooperation, reducing illegal fishing activities, and promoting Indonesia's Indo-Pacific outlook. However, challenges such as implementation gaps, sovereignty disputes, and navigating major power competition persist. The study concludes that sustained maritime diplomacy is critical for Indonesia to realize its full status as a Global Maritime Fulcrum. It also suggests further enhancements in institutional coordination, resource allocation, and international partnerships to solidify its maritime leadership.